Towards a New Model of Work Based Learning in Health and Social Care - Pamela M. Irwin (Adult Education Research Conference, 2006)
Wenger’s (1998) conception of social participation as a process of learning is the most difficult, yet essential, characteristic of health related work based learning programmes to capture. Informed by a socio-cultural perspective, this integrative model of work based learning applies to any participant at any level in any work context.
Keywords: work based learning; health and social care; innovative models of adult education; lifelong learning; practice knowledge